(untitled) (Scientific journal of the Fergana State University, 2025)
This article provides a scientific analysis of the unique characteristics of Uzbekistan’s fuel and energy complex. It highlights the strategic importance of the fuel and energy complex in the national economy, detailing the development status of its key sectors, including oil, gas, coal extraction, and electricity production. Additionally, modern measures aimed at enhancing energy efficiency and utilizing renewable energy sources are proposed.